Effect of quantum mottle on radiographic image quality. - Hendrick WR (Radiologic Technology)
Any critique of radiographic image quality must include an evaluation of quantum mottle, a fundamental limitation of the imaging process. Using an illustrative analogy, this article explains the concept of quantum mottle and defines the quantum sink in an imaging chain. The article also describes the interdependence between quantum mottle and other system parameters, including spatial resolution, contrast resolution and total system speed.